Prinsip-Prinsip Good Corporate Governance, Budaya Tri Hita Karana, dan Kinerja Keuangan LPD - Ni Putu, Eka Tunasti Purnama; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi, 2024)
The purpose of this study was to analyze the effect of the principles of good corporate governance and the tri hita karana culture on the financial performance of the Village Credit Institutions (LPD) in Karangasem Regency. The population used in this study were all Village Credit Institutions in Karangasem Regency, amounting to 190 LPD. The sample in this study was 20 LPD. The method of determining the sample used is purposive sampling method with multiple linear regression analysis technique. The results showed that the principles of good corporate governance consisting of transparency, accountability, responsibility, independence, fairness and tri hita karana culture had a significant positive effect on the financial performance of the Village Credit Institution. The results of this study can provide benefits as input in decision making considerations and can implement the principles of good corporate governance and the tri hita karana culture at the Village Credit Institution, Karangasem Regency. Keywords: Good Corporate Governance Principles; Tri Hita Karana Culture; Financial performance